THE PROBLEM OF PROVING THE INVOLVEMENT OF STATE CIVIL APPARATUS IN REGIONAL HEAD ELECTIONS IN A STRUCTURED, SYSTEMATIC AND MASSIVE MANNER IN DISPUTES IN THE CONSTITUTIONAL COURT - Mora, Diana (Inspiring Law Journal, 2025)
The election of regional heads is a real manifestation of the sovereignty of the people, as stated in Article 18 paragraph (4) of the 1945 Constitution, stating "Governors, Regents, and Mayors are democratically elected as heads of provincial, district, and city governments", in this context, the existence of ASN is very important. It is hoped that ASN can maintain strong neutrality. If it is found that ASN is involved in deliberately supporting one of the candidates, then the ASN will be processed legally. If proven, of course it violates the ASN neutrality rules in Article 2 letter (f) of Law No. 20 of 2023, and this is included in the category of TSM Pilkada violations. So far, the Constitutional Court has rarely decided on Pilkada Results Dispute cases related to TSM ASN involvement. The Constitutional Court should conduct a re-investigation related to the involvement of ASN during the Pilkada, not only listening to statements from the parties, and it is also important to remove the threshold for violations that are TSM in nature, because in reality the Constitutional Court will carry out the proof process if it has met the threshold only, and it is also important to strengthen the implementation of the Pilkada organizing bodies, this is done because the Constitutional Court is the last door for candidates who feel disadvantaged by indications of fraud, and this will have an impact on the community because they get a leader who is not based on an election based on the principles of free and fair elections.